2018
DOI: 10.3390/risks6020054
|View full text |Cite
|
Sign up to set email alerts
|

Diversification and Systemic Risk: A Financial Network Perspective

Abstract: In this paper, we study the implications of diversification in the asset portfolios of banks for financial stability and systemic risk. Adding to the existing literature, we analyse this issue in a network model of the interbank market. We carry out a simulation study that determines the probability of a systemic crisis in the banking network as a function of both the level of diversification, and the connectivity and structure of the financial network. In contrast to earlier studies we find that diversificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…These are "concentration-stability" and "concentration-fragility" hypotheses. The "concentration-stability" hypothesis suggests that there is a significant association between bank concentration and financial stability through profitability channel (Berger, Klapper, & Turk-Aris, 2009;Vives, 2010;Berger & Bouwman, 2013), diversification channel (Frey & Hledik, 2018;Evrensel, 2008) and efficiency channel (Cifter, 2015). Using structural matrix approach on Brazilian data and Hirschman-Herfindahl index to proxy bank concentration Chang, Lima, Guerra, and Tabak (2008) concluded that a concentrated banking system is less prone to a financial crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These are "concentration-stability" and "concentration-fragility" hypotheses. The "concentration-stability" hypothesis suggests that there is a significant association between bank concentration and financial stability through profitability channel (Berger, Klapper, & Turk-Aris, 2009;Vives, 2010;Berger & Bouwman, 2013), diversification channel (Frey & Hledik, 2018;Evrensel, 2008) and efficiency channel (Cifter, 2015). Using structural matrix approach on Brazilian data and Hirschman-Herfindahl index to proxy bank concentration Chang, Lima, Guerra, and Tabak (2008) concluded that a concentrated banking system is less prone to a financial crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We adopt the epidemic model splitting agents affected by idiosyncratic risk from those affected by systemic risk, as previously introduced. We aim to compare the effect of credit risk contagion on two different network structures: the basic model for random graphs, i.e., the Erdös-Rényi for different significant connection probabilities, the core-periphery network for different levels of balance between core nodes and periphery nodes [11], and the small-world networks (Watts-Strogatz networks) for increasing rewiring probability values. In our numerical experiments, we consider a network with 100 nodes in all simulations (it is worth noting that the number of nodes does not influence the results), each of them characterized by a given portfolio with random numbers of assets and correlations.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…As stated in a recent paper [11], the use of random graphs is motivated by the unobservable nature of real-world financial networks. Since the underlying financial network cannot be observed exactly, a probabilistic framework is needed.…”
Section: Introductionmentioning
confidence: 99%
“…A concentrated banking system is able to diversify its portfolio to earn more profits. For instance, using a simulation approach to examine the impact of asset portfolio diversification on financial stability in Austria, Frey and Hledik (2018) conclude that diversification at individual bank level improves financial stability. Furthermore, Fernandez et al (2010) in their study of 84 countries over the period 1980-2004 established that bank size matters when it comes to easy access of information and prevention of adverse selection problems.…”
Section: Previous Evidencementioning
confidence: 99%